PROBLEMATIKA HUKUM PENGGUNAAN TEKNOLOGI NON-FUNGIBLE TOKEN TERHADAP HAK CIPTA - Rohaini, Rohaini; Rusmawati, Dianne Eka; Aisya, Vitania (Legal Standing : Jurnal Ilmu Hukum, 2023)
One form of utilizing the latest digital technology in Copyright is the Non-Fungible Token (NFT). Using a blockchain system to verify the authenticity of works, NFT can be a promising solution for intellectual property protection. However, due to the development of new technologies, research is still needed on how the legal problems of using Non-Fungible Token technology are related to Copyright. This research is a normative juridicial research using primary and secondary data. Data was collected using literature study and internet access, as well as data analysis using qualitative descriptive methods. The results of the research and discussion concluded that NFT technology still has several problems. The problem that occurs in the use of NFT is that there is no related regulation that regulates NFT, so there is no legal certainty to protect the public. Another problem is the theft of copyrighted works belonging to people who are converted into NFT. This is due to the lack of maximum verification of copyrighted works by the NFT marketplace.